Land Capability Assessment of Soils of Bhal-Nal Area of Gujarat Based on Soil Physical Limitations - Patel, J C; Giri, J D (Annals of Arid Zone, 2016)
Studies on some representative soils of Bhal-Nal area of Gujarat have revealed that the soils arc marginally suitable for the crops that arc grown there for several generations. Experiments conducted in the area, and elsewhere. have revealed that the performance of these soils can be improved through certain management practices like deep ploughing. raised bed method of cultivation. larger addition of organic matter, protective irrigation, etc. Certain new crops can be introduced, but their viability has to be experimentally proved through actual demonstration on farmer’s field.